Kierkegaard's concept of self-identity dynamics to awaken spiritual powers: Spiritual counseling perspective - Setiawan, Yohanes Ignasius (ProGCouns: Journal of Professionals in Guidance and Counseling, 2023)
Counselees who take part in spiritual counseling are usually those who are experiencing life impasses. Spiritual counseling offers intervention to reactivate the counselee's spiritual powers. This article aims to look at the possibility of using Soren Kierkegaard's thought of self-identity dynamics as a framework for spiritual counseling interventions. Kierkegaard, who is known as an existentialist philosopher, considers that human self-identity has three dimensions. First, the synthesis of two opposite poles: between the infinite and the finite, the mortal and the eternal, freedom and necessity. Second, internal relations: relations that connect oneself and one's individuality. The third is deep dependence on the transcendent. The three dimensions of human identity are in harmony with the main character of spiritual counseling. The method used to see this possibility is a literature study. The author reviews various literature related to spiritual counseling and Kierkegaard's concept of self-identity dynamics to produce a comprehensive discussion. There are ten journal articles that the author used for this research. Three main discussions of this paper are the definition of spiritual counseling, the concept of Kierkegaard's Self-identity dynamics, and the application of Kierkegaard's self-identity dynamics to spiritual counseling. The discussion concluded that Kierkegaard's thoughts on self-identity provided an adequate framework for the dynamics of spiritual counseling, especially to help counselees realize and actualize spiritual powers to build wholeness in freedom. This study will benefit spiritual counselors to deal with counselees experiencing life impasses and to broadenthe counselor's understanding in facilitating the counseling process.